Analytical method using gamma functions for determining areas of power elliptical shapes for use in geometrical textile models - Gommer, Frank; Brown, Louise P.; Wedgwood, Kyle C.A. (Elsevier, 2015)
Textile models are often assumed to have homogenous and well defined cross-sections. For these models, the use of a power elliptical cross-sectional shape has been found to be beneficial as different shapes can be created, e.g. lenticular, elliptical or rectangular, with a single function. The cross-sectional area of a power ellipse is usually determined numerically as the analytical determination of the cross-sectional area is not straightforward. This short communication presents an analytical solution for this shape.